Extracellular matrix remodeling in idiopathic pulmonary fibrosis. It is the 'bed' that counts and not 'the sleepers'. (3rd April 2017) - Tomos, Ioannis P.; Tzouvelekis, Argyrios; Aidinis, Vassilis; Manali, Effrosyni D.; Bouros, Evangelos; Bouros, Demosthenes; Papiris, Spyros A.
ABSTRACT: Introduction : Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive interstitial lung disease characterized by irreversible fibrosis. Current disease pathogenesis assumes an aberrant wound healing process in response to repetitive injurious stimuli leading to apoptosis of epithelial cells, activation of fibroblasts and accumulation of extracellular matrix (ECM). Particularly, lung ECM is a highly dynamic structure that lies at the core of several physiological and developmental pathways. The scope of this review article is to summarize current knowledge on the role of ECM in the pathogenesis of IPF, unravel novel mechanistic data and identify future more effective therapeutic targets. Areas covered : The exact mechanisms through which lung microenvironment activates fibroblasts and inflammatory cells, regulates profibrotic signaling cascades through growth factors, integrins and degradation enzymes ultimately leading to excessive matrix deposition are discussed. Furthermore, the potential therapeutic usefulness of specific inhibitors of matrix deposition or activators of matrix degradation pathways are also presented. Expert commentary : With a gradually increasing worldwide incidence IPF still present a major challenge in clinical research due to its unknown etiopathogenesis and current ineffective treatment approaches. Today, there is an amenable need for more effective therapeutic targets and ECM components may represent one.